A Review of X-linked Charcot-Marie-Tooth Disease. (May 2016) - Wang, Ying; Yin, Fei
X-linked Charcot-Marie-Tooth disease (CMTX) is the second common genetic variant of CMT. CMTX type 1 causes 90% of CMTX. The most important clinical features of CMTX are similar with other types of CMT; however, a few patients get the central nervous system involved with or without white matter lesions; males are more severely and earlier affected than females. In this review, the authors focus on the origin and classification of CMTX, the central nervous system manifestations of CMTX1, the possible mechanism by which GJB1 mutations cause CMT1X, and the emerging therapeutic strategies for CMTX. Moreover, several cases are presented to illustrate the central nervous system manifestations.